2019
DOI: 10.1111/1365-2435.13252
|View full text |Cite
|
Sign up to set email alerts
|

Foliar phosphorus fractions reveal how tropical plants maintain photosynthetic rates despite low soil phosphorus availability

Abstract: Nitrogen (N) and phosphorus (P) are essential nutrients for plant metabolism, and their availability often limits primary productivity. Whereas the effects of N availability on photosynthetic capacity are well established, we still know relatively little about the effects of P availability at a foliar level, especially in P‐limited tropical forests. We examined photosynthetic capacity, leaf mass per area (LMA) and foliar P fractions in five woody plant species after 6 years of N and P fertilization in a lowlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 47 publications
(107 reference statements)
6
81
0
1
Order By: Relevance
“…We show small trees can increase J max , but not V cmax , without additional leaf nitrogen or phosphorus (Figure 1), most likely by increasing nutrient use efficiency (Figure 3). This may occur via a potential re-allocation of nitrogen and phosphorus to optimize photosynthetic capacity (Hasper et al, 2017;Mo et al, 2019). The carboxylation reactions have greater nutrient demand for enzymes, such as RuBisCO, compared to those in the electron transport chain (Evans, 1989;Raven, 2013;Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We show small trees can increase J max , but not V cmax , without additional leaf nitrogen or phosphorus (Figure 1), most likely by increasing nutrient use efficiency (Figure 3). This may occur via a potential re-allocation of nitrogen and phosphorus to optimize photosynthetic capacity (Hasper et al, 2017;Mo et al, 2019). The carboxylation reactions have greater nutrient demand for enzymes, such as RuBisCO, compared to those in the electron transport chain (Evans, 1989;Raven, 2013;Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Plants grown with different phosphate nutrition are therefore not significantly more or less likely to experience TPU limitation. Most phosphate in photosynthesizing cells will be used in nucleic acids and phospholipids (Dissanayaka et al, 2018), and growth is more sensitive to phosphate nutrition than is photosynthetic rate (Mo et al, 2018). Ellsworth et al (2015) showed that Australian plants growing in the wild with varying phosphate availability were adapted to their environment, and TPU limitation was more likely at high phosphate nutrition.…”
Section: Tpu and Plant Nutritionmentioning
confidence: 99%
“…Furthermore, in the P addition treatment there was a marginally significant negative relationship between P affinity and the increase in foliar P concentration between ambient and elevated CO 2 . In a fertilization experiment in lowland tropical China, P addition increased all four functional types of foliar P: structural P, metabolic P, nucleic acid P and residual P of tropical trees (Mo et al, ). The magnitude of change was species‐specific, but species could reallocate P pools to meet photosynthetic demands (Mo et al, ), suggesting that some species may be able to overcome P limitation of certain responses in P‐poor soils.…”
Section: Discussionmentioning
confidence: 99%
“…In a fertilization experiment in lowland tropical China, P addition increased all four functional types of foliar P: structural P, metabolic P, nucleic acid P and residual P of tropical trees (Mo et al, ). The magnitude of change was species‐specific, but species could reallocate P pools to meet photosynthetic demands (Mo et al, ), suggesting that some species may be able to overcome P limitation of certain responses in P‐poor soils. These results highlight the need for further studies to understand the differences in species PUE or P uptake mechanisms that allow species to thrive in low‐P environments and specifically how they may affect species responses to elevated CO 2 .…”
Section: Discussionmentioning
confidence: 99%